Perbandingan Sistem Hukum Indonesia dan Australia Tentang Pengaturan Pertimbangan Bisnis (Business Judgement) - Muninggar, Roro Ajeng; Saleh, Rosdiana (UNES Law Review, 2024)
The legal systems adopted by Indonesia and Australia have differences, Indonesia adheres to civil law while Australia adheres to common law. The author in this study intends to conduct a comparative study of the legal system between Indonesia and Australia regarding business judgment arrangements. The issues studied are about the similarities and differences between business judgment arrangements in Indonesia and Australia, as well as the factors that cause these similarities and differences. The author uses normative methods by using a legal approach in the preparation of this study. The results of the comparison of legal systems between Indonesia and Australia have similarities, namely in terms of legal rules where both already have written legal rules, and the second in terms of regulating business judgment for the Board of Directors, while the differences that are seen are different legal systems, implementation of written rules, origin of rules, substance of rules, and position of jurisprudence. The factors that cause these similarities and differences include historical factors of the country, thinking characteristics, and economics.